Quantum mechanics I - Walet, Niels (The University of Hull)
A set of resources (lecture notes, exercises and figures) linked to a second year course in quantum mechanics. Both processed files (html/xhtml/pdf) and the raw inputs are provided, together with scripts to convert the material. Part of the Skills for Scientists project.